Let’s not rock the boat. Frauenorganisationen und Demokratisierung in Malaysia - Spiegel, Anna; Dannecker, Petra (Internationales Asienforum)

Alltagswelten in translokalen Räumen : Bolivianische Migrantinnen in Buenos Aires - Spiegel, Anna
Am Beispiel bolivianischer Migrantinnen in der Global City Buenos Aires wird das Phänomen der Feminisierung der Migration in Lateinamerika und dessen Bedeutung für die Konstitution translokaler sozialer Räume untersucht. Im Mittelpunkt einer {\glq}dichten Beschreibung’ pluri-lokaler Alltagswelten stehen dabei ökonomische Netzwerke und translokale Lebensentwürfe von Arbeiterinnen in illegalen Textilsweatshops und Frauen der Töchtergeneration. Analysiert werden einerseits die alltagsweltlichen sozialen Praktiken von Migrantinnen, die zu einer Kon-stitution eines translokalen und kulturell hybriden Raumes zwischen den beiden Nationalgesell-schaften Bolivien und Argentinien Raumes beitragen und andererseits Prozesse und Dynamiken der Neuaushandlung von ethnischen Identitäten in einem solchen Raum. Probing into the lives of female Bolivian migrants in the global city Buenos Aires, this empirical research explores feminisation of migration in Latin America analysing its significance for the constitution of translocal social spaces. Applying {\grq}thick description’ to the migrants’ pluri-local life worlds, the study closely examines how Bolivian women in Buenos Aires, partly working in illegal sweatshops and partly second generation migrants, establish economic networks and set up their translocal life plans. Thus the analysis of the migrants’ everyday social practices, such as work and leisure, yields insight not only into the constitution of a translocal and cultur-ally hybrid social space between the two countries, but also into dynamics of re-negotiation of ethnic identities within this space.
Keywords: Alltag; Bolivianische Einwanderin; Buenos Aires; EthnizitÃ¤t

Negotiating Development: Trans-local Gendered Spaces in Muslim Societies - Nageeb, Salma; Sieveking, Nadine; Spiegel, Anna

Engendering Development in Muslim Societies: Actors, Discourses and Networks in Malaysia, Senegal and Sudan - Nageeb, Salma; Sieveking, Nadine; Spiegel, Anna

Beyond Cultural Differences: 'Intercultural' Co-operation in a German/Sri Lankan Development Project - Knoll, Lisa (Internationales Asienforum)
As development co-operation is most of the time 'intercultural' co-operation, behaviour is frequently explained by cultural arguments. I argue that regarding behaviour as being generated by cultural origin precludes integration in a conglomerate of structural dependencies and formal and informal relationships. It is argued that culture is first of all a powerful and persuasive discourse in development co-operation and that it provides orientation in complex working situations. 'Hide-and-seek' and 'discussing openly' - behavioural patterns considered to be either typically Sri Lankan (Eastern) or typically German (Western) - are presented in order to show that culture is a reciprocal process of identity creation rather than a feasible explanation of behaviour. The structural integrations of project collaborators show that behaviour in a ' hide-and-seek' manner more likely reflects dependencies in a counterpart set-up than to cultural origin.

Gender and Translocal Networking through Information Technology - Spiegel, Anna; Nadine, Harig

Public Spheres, Public Islam, and Modernities - Spiegel, Anna